STRATEGI PERENCANAAN PENINGKATAN PENYALURAN KREDIT DAN PERKEMBANGAN BPRS DI JAWA TIMUR YANG TERDAFTAR PADA BANK INDONESIA - Elsa Dwi Jayanti (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
The role of banks in addition to acting as a collector and channeling of funds is also very important in supporting the welfare sector of Small and Medium Enterprises. The level of BPR Sharia competition can be known by looking at the market share of Territory. According to the Banking Act No.10 of 1998, the type of banking industry that runs its business based on sharia principles, which has characteristics closer to the community due to small market share and easy funds. This study aims to classify the research object used is BPR Sharia in East Java. The number of BPR Sharia used in this study amounted to 28 BPR Sharia existing in 18 districts that publish the financial statements regularly in 2017. Through variables CAR, KAP, NPF, BOPO, and FDR. From the above developments data can be grouped in matrix with the provisions in accordance with Bank Indonesia Regulation No.SE.13/1/PBI/2011. cluster 1 is group of BPRS A with fluctuation condition and cluster 2 is group of BPR Sharia B with very good condition. Both clusters have alternative strategies for each BPR Sharia group in increasing lending. Thus in this research will be formulated operational strategy for both groups using SWOT analysis.